The Use of - R Control Chart on The Filling Process at A Particular Pasteurized Milk Industry in Malang - Santoso, E.F. Sri Maryani; Deoranto, Panji; Mahfudiana, Dwi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
The purposes of this research were to develop an - R control chart of the filling process in a particular pasteurized milk industry in order to improve the performance of the process. Based on the data of the milk volume filled in the container, the - R control chart of the filling process was developed. It was found that an average volume ( ) was 143.88 ml; and the respective values of UCL and LCL were 147.74 ml and 140.52ml, with an average volume range (R) of 5.83 ml; UCLR = 12.30 ml; and LCLR = 0. The chart showed that the center line and limits of the X control exceeded the predetermined value of 140 ± 5 ml, with the average volume of 143.88 ml, which was above the set value of volume 140 ml. The value of Cp was 0.66 (less than 1,00) and the Kane performance index, CPK = 0,15 which was equal to the CPU. It means that the operation of the filling process was under its capacity. Since the filling machine used was a semi automatic one, to reduce the excessive filling may be carried out either by upgrading operator or machinery performances.Key word: control chart, filling process, pasteurized milk